2022
DOI: 10.1515/chem-2022-0155
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiling, antibacterial and antioxidant properties of Crocus sativus flower: A comparison between tepals and stigmas

Abstract: Several studies have demonstrated that stigmas of Crocus sativus contain several bioactive compounds with potential health-promoting properties. However, during the processing of stigmas, large amounts of floral bio-residues are normally discarded as by-products. In this study, using untargeted metabolomics, the comprehensive phytochemical composition of C. sativus stigma and tepals was investigated. Moreover, the antibacterial and anti-biofilm properties of the extracts of C. sativus stigmas and tepals were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…However, the values obtained appear higher than those reported by Asgarpanah et al for methanolic extracts of Iranian saffron petals (4.09 to 17.34 mg GAE/g MS) [ 40 ]. Although some studies have shown that petals of Crocus sativus L. contain more polyphenols than stigmas [ 39 , 41 ], other studies have reported the opposite, with a concentration of 97.99 mg GAE/g for stigmas and 69.18 mg GAE/g for petals [ 42 ]. Thus, there is no clear consensus as to which of these floral parts of Crocus sativus L. contain the highest polyphenol content.…”
Section: Resultsmentioning
confidence: 99%
“…However, the values obtained appear higher than those reported by Asgarpanah et al for methanolic extracts of Iranian saffron petals (4.09 to 17.34 mg GAE/g MS) [ 40 ]. Although some studies have shown that petals of Crocus sativus L. contain more polyphenols than stigmas [ 39 , 41 ], other studies have reported the opposite, with a concentration of 97.99 mg GAE/g for stigmas and 69.18 mg GAE/g for petals [ 42 ]. Thus, there is no clear consensus as to which of these floral parts of Crocus sativus L. contain the highest polyphenol content.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for more polar compounds, an attempt could be made to dilute plant samples in the case of the need of usage selected extractants for the process of extracting bioactive compounds from a given plant [ 1 , 31 , 32 ]. A good example is the separation of an isopropanol-based extract [ 33 , 34 ], which is less polar than methanol but still belongs to compounds with a high dipole momentum.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed significant reductions in the numbers of bacterial cells, and when the pathogens were incubated with saffron stamen extracts at 6 °C, a synergistic effect was observed. 11 Bellachioma et al 55 compared the antimicrobial activities of saffron petal and stigma extracts, and reported that the antimicrobial activity of the petal extracts was stronger than stigma extracts. Asgarpanah et al 88 also observed that methanol extracts of saffron petals had stronger antimicrobial activity against certain pathogens, including Staphylococcus aureus, Salmonella enterica, and Shigella dysenteriae, when compared with stigma extracts.…”
Section: •−mentioning
confidence: 99%
“…The antioxidant properties of different parts of the saffron plant also differ. Generally, petal extracts show good antioxidant activity, even higher than extracts of the stigma or stamen. ,, Mir et al reported that petals had the highest antioxidant activity, followed by leaves, stamens, and styles. Serrano-Díaz et al demonstrated that the stamens showed the strongest scavenging ability for LOO • and OH • free radicals, even higher than propyl gallate.…”
Section: Biological Activities Of Saffron Byproductsmentioning
confidence: 99%
See 1 more Smart Citation